The Simile according to Abu Dharr Musab bin Masoud Al-Khushni (d. 604) in His Book Al-Imlah Al-Mukhtasar fi Sharh Gharib Al-Sir - Muhammad, Noha Jassim; khalaf, Abdel Wahab Hussein (Journal of Tikrit University for Humanities, 2024)
This research deals with simile, which is one of the basic sections of the science of rhetoric. It is based on extracting the rhetorical purposes of simile and explain their types in the book Brief Dictation in Explanation of Gharib Al-Sir, and what indicates its importance due to its frequent occurrence in the Holy Qur’an and the noble hadiths of the Prophet, the words of the Arabs, and Arabic poetry through the use of poetic images that poets used to highlight their ideas, meanings, and lives in different methods, as Al-Khushani took a careful and precise stance on many issues of simile through his explanation of the stranger who was mentioned in the biography of the Prophet by Ibn Hisham.